Medicinal Plant Images - Cock, Ian E (Pharmacognosy Communications)
Australian Acacia spp. The genus Acacia (family Fabaceae) is a large genus of more than 1200 trees and shrubs which are widely distributed throughout the world, with more than 700 species indigenous to Australia. The Australian species had multiple medicinal uses by indigenous Australians, including being used to treat diarrhoea and hyperglycemia1,2 and as a general antiseptic agent.4-7 Many Australian acacia species have been reported to have amtimicrobial, molluskicidal, antihypertensive and platelet aggregatory activities.1 This photograph was taken in Brisbane, Australia in 2024 by Dr. Ian Cock.